2003
DOI: 10.1038/nmat930
|View full text |Cite
|
Sign up to set email alerts
|

The remarkable difference between surface and step atoms in the magnetic anisotropy of two-dimensional nanostructures

Abstract: ARTICLES 546nature materials | VOL 2 | AUGUST 2003 | www.nature.com/naturematerials E xploring the ultimate density limits of magnetic information storage, whether on computer hard disks or in MRAMs (magnetic random access memories), requires elaborate tuning of the preferred (easy) magnetization axis, of the magnetic anisotropy energy, and of the magnetic moment in the units used to store a bit. These units are single-domain particles (with diameter d < 20 nm) where the magnetic moments of all atoms are ferro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
212
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(231 citation statements)
references
References 28 publications
18
212
0
1
Order By: Relevance
“…19,27 With the experimental techniques now available, nanowires and nanostructures may be deposited on magnetic and nonmagnetic surfaces in a controlled fashion, and their fundamental magnetic properties can be explored with the use of advanced experimental methods. [28][29][30][31][32][33][34] From the above discussions, it is quite evident that the magnetic interactions at the interface between Mn and Fe have a very rich variety depending on the geometry and local environment. Particularly, the study of the nanostructures of Mn supported on Fe is quite fascinating.…”
Section: Introductionmentioning
confidence: 99%
“…19,27 With the experimental techniques now available, nanowires and nanostructures may be deposited on magnetic and nonmagnetic surfaces in a controlled fashion, and their fundamental magnetic properties can be explored with the use of advanced experimental methods. [28][29][30][31][32][33][34] From the above discussions, it is quite evident that the magnetic interactions at the interface between Mn and Fe have a very rich variety depending on the geometry and local environment. Particularly, the study of the nanostructures of Mn supported on Fe is quite fascinating.…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, experiments have shown that low C N atoms play a pivotal role. 9,10 When the particle's size is reduced to only 10À20 Å, two main challenges are posed: (i) the formation in a controllable and reproducible manner of large-scale replicas of these individual building blocks on a suitable substrate 11 and (ii) the determination and tuning of the geometric and electronic structure of the supported nanoobjects.One of the most recent solutions to meet the first challenge is to make use of template graphene (GR) for the growth of metallic nanoclusters and for the formation of long-range-ordered superstructures. This * Address correspondence to alessandro.baraldi@elettra.trieste.it.…”
mentioning
confidence: 99%
“…In this respect, experiments have shown that low C N atoms play a pivotal role. 9,10 When the particle's size is reduced to only 10À20 Å, two main challenges are posed: (i) the formation in a controllable and reproducible manner of large-scale replicas of these individual building blocks on a suitable substrate 11 and (ii) the determination and tuning of the geometric and electronic structure of the supported nanoobjects.…”
mentioning
confidence: 99%
“…The observed MAE distributions becomes sharper when the volume of the Co nanodot increases, which is assigned to a more homogeneous volume distribution for larger nanodots, as seen in the STM analysis. Notably, K is not observed to scale with the number of atoms N in the dot, but rather with N, in a similar way as observed for Co nanodots on Au(788) or Pt(111) 9, 40. This can be explained by an anisotropy constant K that is mainly determined by perimeter atoms, which have lower coordination.…”
Section: Resultsmentioning
confidence: 54%
“…Considering the number of perimeter atoms deduced from the STM images (see Supporting Information), we obtain that K p is approximately (1.25 ± 0.2) meV/atom for 0.4 ML and 0.9 ML nanodot arrays, and it is slightly reduced to K p = (1.1 ± 0.2) meV/atom for the 1.3 ML array. Thus, K is notably larger in Co nanodots grown on trigons than in those grown on Pt(111), Au(788), or Au(11,12,12) [0.8–0.9 meV/atom] 3, 9, 40…”
Section: Resultsmentioning
confidence: 99%